Characteristics of Fluorescent Dissolved Organic Matter in Paddy Soil Amended With Crop Residues After Column (0–40 cm) Leaching - Gao, Jiakai; Liu, Ling; Shi, Zhaoyong; Lv, Jialong (Frontiers in Environmental Science, 2022)
Dissolved organic matter (DOM) has a critical impact on various processes in ecological environment, especially in soil and surface water due to its mobility and reactivity. In the present study, a column experiment simulating a paddy field was conducted to evaluate the feasible application of inorganic fertilizer incorporated with three types of organic materials (Wheat straw, Rapeseed shell and Astragalus smicus). Researchers investigated the vertical distinctions of soil (combined with different organic materials in 0-10 cm) DOM in 0-40 cm profiles after a long-term leaching. Excitation-emission matrices coupled with parallel factor analyses (EEM-PARAFAC) and UV-visible techniques were employed to diagnose the spectral characteristics of soil DOM at the four depths in different treatments, qualitatively and quantitatively. The results showed DOM content of CF (Conventional fertilizer) (0.14 g kg-1) was the highest at 10-20 cm layer and the CK (No fertilizer) (0.05 g kg-1) at 30-40 cm was the lowest, and the mean DOC concentration decreased with the increase of soil depth. Four fluorescent components, protein and tryptophan-like, humic acid-like, fulvic acid-like and solubility-like microbial metabolites products materials, were identified by PARAFAC model. Relative distributions of calculated components suggested DOM mainly contained more aromatic humic materials and litter fulvic acid with the increase of soil depth. However, the SUVA254 showed a maximum in 20-30 cm layers, indicating strong aromatic and abundant hydrop hobic fractions. Fluorescent index (FI) values of soil DOM from various treatments have similar terrestrial and allochthonous source in topsoil and microbial source in deeper soil. In short, the findings obtained in our work could commendably provide some valuable and advisable optical information of DOM released from soil column and offer technical guidance when applying organic or green fertilizer to paddy soil in the duration of rice production.